The effect of differing types of cloth and of contamination by non-feed nitrogen on intestinal digestion estimates using porous synthetic-fibre bags in a cow - Varvikko, T.; Vanhatalo, A. (Cambridge University Press, 1990)
The influence of free surface area and pore size of a synthetic-fibre bag, and flow of intestinal substances into the bag, on the intestinal digestion estimates by the nylon-bag method of dry matter (DM), neutral detergent fibre (NDF), nitrogen, NDF-N and feed 15N was studied using a non-lactating cow fed on hay supplemented with barley and oats at maintenance level. The bags containing 15N-labelled ground ryegrass (Lolium perenne), barley, barley straw or rapeseed (Brassica napus) straw were introduced into the duodenum through a T-shaped cannula and collected from the faeces. Also, the disappearance of N from the bag was related to the true intestinal N digestion by comparing it with the net loss between duodenum and faeces of 15N in ryegrass introduced into the duodenum in an aqueous suspension. It was noted that the bag cloth often significantly affected both disappearance values and the subsequent chemical composition of the residues. Re-analysing part of the data as a 2x2 factorial (free surface x pore size) suggested that free surface area was often more important than pore size as a determinant of both disappearance values and chemical composition. Lower apparent (Kjeldahl N) than true (15N) feed N disappearance from the bag suggested a notable proportion of non-feed N in the residues, especially with fibrous feeds with low N. With ryegrass, 15N net loss within the intestine was lower than 15N disappearance from the bags. It was concluded that disappearance of Kjeldahl N is an underestimate of feed N disappearance from bags, but may possibly be an overestimate of the true intestinal digestion of feed N.